Transformation of political elite as regime changes in Pakistan - Shoukat, Ayesha; Gomez, Edmund Terence (Taylor & Francis, 2018)
Burton and Higely [(2001). ‘The study of political elite transformations’, International review of sociology/Revue internationale de sociologie, 11(2): 181–199] argue that when elites of a society are not united this will lead to an unstable political regime. Consensual elite cohesion is only created through distinctive elite transformation. This essay attempts to elaborate their argument in Pakistan, by developing a link among a continuous regime shift from authoritarian to democratic governments and the political elites who keep transforming their structure accordingly. The technique followed for it is analysing the epochal events over time from pre-partition till date which became reason for regime transformations. The discussion focuses on the collusions and contestations of multiple power elites within given social context which are embedded under the international context. It concludes that political elites in Pakistan were always embraced by multiple other power elites who accordingly hold dual elite identity to control the command post in the political arena. Such complex elite structure makes it paradoxical to distinguish political elite of Pakistan from other power elites of Pakistan.